The Vanishing Acheron House of Refuge. A Case of "Frontier Chaos"? - Kelly, Clare (Architectural History Aotearoa, 2010)
The Acheron House of Refuge built between 1863 and 1864 near the junction of the Guide River with the Acheron River in the South Island high country was one of a chain of accommodation houses on the Inland Stock Route between Nelson and Canterbury. In 1865 the Nelson Provincial Engineer John Blackett wrote to the Nelson Provincial Government that he feared "the entire destruction of the house without the possibility of it being prevented" and blamed "the character of some of the travellers who pass this road." By the end of 1865, it was destroyed without trace. This paper considers incidents of lawlessness at the accommodation houses in the mid 1860s and the brief existence of the Acheron House of Refuge. It questions whether its demise was the result of "frontier chaos," a term which was first used by historian Miles Fairburn in 1989 to describe how rapid frontier expansion in New Zealand had scattered settlers and engendered transience, loneliness and lawlessness. Using settler diaries, letters and manuscripts this paper considers Fairburn's "frontier chaos" theory. It examines his assertions that in the New Zealand settler world prior to 1890 "seldom ... were goods and services exchanged," and that an atomised New Zealand settler society had "no institutions ... to facilitate mixing and meeting" (Fairburn "Local Community or Atomised Society?" pp 169-170,192,195,206,217). This paper concludes that incidents of lawlessness at the accommodation houses were linked to the South Island gold rushes, were short term and often the result of ill-prepared men desperate to survive in an unforgiving climate. At the accommodation houses on the Nelson to Canterbury Inland Stock Route travellers, keepers and neighbours shared an unwritten code of reciprocity. These accommodation houses formed the unofficial nuclei of small, loose-knit high country communities.